Basin or Intrusion, a New Method to Resolve Non-Uniqueness in Gravity Interpretation - AL-Rahim, Ali M.; A. Lima, Williams (Iraqi Journal of Science, 2023)
The aim of the current paper is to resolve the non-uniqueness in gravity interpretation through searching for singular points in the gravity field that are coincide with causative body vertices. The Absolute Second Horizontal Gradient (ASHG) method is used to locate the horizontal reference location of the body, while its amplitude could be used to define body corner depth. Intelligent use of the ASHG method could help in differentiating between basin and intrusion structures from their gravity effect and could facilitate the interpretation in forward modeling and constrain inversion modeling to maximum limit. The method is tested by using many synthetic examples with different types of shapes. A real data is used to examine the method and give a decisive result about the type and shape of the causative body.